Modelagem e Desenvolvimento de Jogos Móveis Baseados em Localização - Ferreira , Cristiane; Viana, Windson; Trinta, Fernando (Anais Estendidos do Simpósio Brasileiro de Sistemas Multimídia e Web (WebMedia), 2016)
A Pervasive Game is based on a combination of hybrid interfaces involving mobile devices, wireless networks, positioning systems and context sensing technologies. Location-Based Mobile Games (LBMGs) are a subclass of pervasive games. They make use of location technologies and add the position of their players in the game rules. A state of the art survey involving locative mobile games, LBMGs authoring tools, and modeling pervasive games was conducted. This research aims at presenting a language that allows the representation of LBMGs and the media used in the mechanics of these games. We want to support temporal aspects, as well as, spatial relationships. Also, the research will investigate checking mechanisms for generating LBMGs to be incorporated into LAGARTO tool.